Gehua Jiecheng Decoction Inhibits Diethylnitrosamine-Induced Hepatocellular Carcinoma in Mice by Improving Tumor Immunosuppression Microenvironment - Cheng, Changpei; Shou, Qiyang; Lang, Jiali; Jin, Lu; Liu, Xia; Tang, Dongxin; Yang, Zhu; Fu, Huiying (Frontiers in Pharmacology, 2020)
Gehua Jiecheng Decoction (GHJCD), a famous traditional Chinese medicine, has been used in the prevention and treatment of precancerous lesion of liver cancer, but its active mechanism has not been reported. This study aimed to evaluate the therapeutic effect of GHJCD on diethylnitrosamine-induced hepatocellular carcinoma (HCC) in mice and the mechanism of this effect. We found that GHJCD effectively inhibited the occurrence of liver cancer and reduced the tumor area. The ratio of regulatory cells (Tregs), tumor associated macrophage(TAMs), and myeloid-derived suppressor cells(MDSCs) in HCC microenvironment was downregulated, whereas that of CD8 T and effective CD8 T cells was upregulated. In addition, the expression levels of inflammatory factors IL-6, IL-10, TNF-α, and CCL-2 in the liver were inhibited, whereas those of the angiogenesis related molecules CD31 and VEGF were decreased. Moreover, wnt1, β-catenin, NF-kB, p-MAPK, p-AKT, and p-SRC content in the liver decreased, whereas APC content increased. These results suggested that GHJCD exerted a good inhibitory effect on liver cancer induced by diethylnitrosamine, and thus may have a multi-target effect; GHJCD not only antagonized the immunosuppressive effect of the microenvironment of liver cancer but also exerted strong anti-inflammatory and antiangiogenesis effects.